Trends and Outcomes of ST‐Segment–Elevation Myocardial Infarction Among Young Women in the United States - Temidayo Abe; Titilope Olanipekun; Demilade Adedinsewo; Oluseye Ogunmoroti; Ndausung Udongwo; Valery Effoe; Bria Rice; Ifeoma Onuorah; Jalal K. Ghali; Puja K. Mehta; Erin D. Michos (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Although there has been a decrease in the incidence of ST‐segment–elevation myocardial infarction (STEMI) in the United States, this trend might be stagnant or increasing in young women. We assessed the trends, characteristics, and outcomes of STEMI in women aged 18 to 55 years. Methods and Results We identified 177 602 women aged 18 to 55 with the primary diagnosis of STEMI from the National Inpatient Sample during years 2008 to 2019. We performed trend analyses to assess hospitalization rates, cardiovascular disease (CVD) risk factor profile, and in‐hospital outcomes stratified by three age subgroups (18–34, 35–44, and 45–55 years). We found STEMI hospitalization rates were decreased in the overall study cohort from 52 per 100 000 hospitalizations in 2008 to 36 per 100 000 in 2019. This was driven by decreased proportion of hospitalizations in women aged 45 to 55 years (74.2% to–71.7%; P<0.001). Proportion of STEMI hospitalizationincreased in women aged 18–34 (4.7%–5.5%; P<0.001) and 35–44 years (21.2%–22.7%; P<0.001). The prevalence of traditional and non‐traditional female‐specific or female‐predominant CVD risk factors increased in all age subgroups. The adjusted odds of in‐hospital mortality in the overall study cohort and age subgroups were unchanged throughout the study period. Additionally, we observed an increase in the adjusted odds of cardiogenic shock, acute stroke, and acute kidney injury in the overall cohort over the study period. Conclusions STEMI hospitalizations are increasing among women aged <45 years, and in‐hospital mortality has not changed over the past 12 years in women aged <55 years. Future studies on the optimization of risk assessment and management of STEMI in young women are urgently needed.